ASMA : LAPORAN KASUS - Dewi Murni Manihuruk (Collaborative Medical Journal, 2024)
A 46 year old female patient came to the emergency department of the hospital with complaints of shortness of breath since 4 days ago. Shortness of breath accompanied by a 'whimpling' sound that disappears becomes worse during activity and in cold weather. History of long-standing cough and history of trauma were denied. The patient has the same history since 28 years ago. On examination of vital signs, blood pressure, pulse and temperature were found to be within normal limits, respiratory rate 22 x/minute, SpO2 95%. The patient's nutritional status is 36.3 (grade II obesity). Physical examination of the chest inspection was symmetrical, on palpation palpable symmetrical tactile fremitus, sonor percussion in both lung fields, and additional wheezing breath sounds in both lung fields. The patient undergoes supporting examinations in the form of routine blood laboratory examinations, BTA examinations, and X-ray examinations. The results of the routine blood laboratory examination were within normal limits, the TCM TB examination was not detected. Chest x-ray examination with the impression of pulmonary fibrosis and EC calcification (former pulmonary TB). The patient was diagnosed as having an asthma exacerbation. In patients who do, treat with bronchodilator drugs or systemic corticosteroids.